European Storm Petrels Hydrobates pelagicus visiting the Swedish west coast; results from a ringing study 1988—2012 - Ström, Kåre; Niklasson, Aimon (Ornis Svecica, 2014)
The results of a 25 year study of the Storm Petrel Hydrobates pelagicus on the Swedish west coast are described. The first bird was captured on 29 August 1988 (Orust in Bohuslän). A total of 72 Storm Petrels were captured between 1988 and 2012 (64 in Bohuslän and 8 in Halland). Sixty-eight of these were ringed by us and 4 were ringed abroad. Thirteen Storm Petrels ( 18%) were captured twice or thrice: 4 re-traps by us (ringed abroad, 3 in Norway, 1 in Britain), 2 own re-traps and 6 recaptured abroad (2 in Britain and 4 in Norway; one own ringed bird recaptured twice). Three additional birds were spontaneously captured in other studies in southern Sweden during the same period. Mean body mass (SD) was 25.5 (1.9) g, and wing length was 123.1 (2.6) mm. A concentration of birds during the turn of the millennium may be related to periods of upwelling. Still no birds have been found breeding in Sweden. Comments are made regarding the first description by Linnaeus.